Influence of Cardiovascular Risk Burden on Motor Function Among Older Adults: Mediating Role of Cardiovascular Diseases Accumulation and Cognitive Decline - Wang, Zhangyu; Cui, Kaiwang; Song, Ruixue; Li, Xuerui; Qi, Xiuying; Buchman, Aron S.; Bennett, David A.; Xu, Weili (Frontiers in Medicine, 2022)
PURPOSE: This study aimed to investigate the association of the cardiovascular risk burden assessed by the Framingham general cardiovascular risk score (FGCRS) with the trajectories of motor function over time and to assess the mediating effects of cardiovascular diseases (CVDs) accumulation and cognitive decline in such association. METHODS: Within Rush Memory and Aging Project, a total of 1,378 physical-health participants (mean age: 79.3±7.3 years) were followed for up to 22 years. FGCRS at baseline was assessed and categorized into tertiles (lowest, middle and highest). Global motor function (including dexterity, gait, and hand strength) was assessed annually with 10 motor tests. CVDs (including stroke, congestive heart failure, and other heart diseases) were ascertained at baseline and follow-ups, and the number of CVDs accumulation over time was assessed. Global cognitive function was tested annually by 19 tests. Data were analyzed using the linear mixed-effects models and mediation analysis. RESULTS: At baseline, FGCRS was ranged from 4 to 28 (mean score: 15.6± 3.7). Over the follow-up (median, 5.3 years; interquartile range, 2.9-9.0 years), in multi-adjusted mixed-effects models, the highest FGCRS was associated with faster decline in global motor function (β= -0.0038; 95% confidence interval [CI]: -0.0069 to -0.0008), dexterity (β= -0.0056; 95% CI: -0.0093 to -0.0020), gait (β= -0.0039; 95% CI: -0.0077 to -0.0001), and hand strength (β= -0.0053; 95% CI: -0.0098 to -0.0008) compared to the lowest tertile. In mediation analysis, CVDs accumulation and cognitive decline mediated 8.4% and 42.9% the association between FGCRS and global motor function over time, respectively. CONCLUSIONS: Higher cardiovascular risk burden is associated with faster decline in motor function including dexterity, gait, and hand strength. CVDs accumulation and cognitive decline may partially mediate the association between cardiovascular risk burden and global motor function decline.